Applied process control : efficient problem solving - Mulholland, M. (Weinheim, Germany : Wiley-VCH Verlag GmbH & Co. KGaA, 2016)
Bridging theory and practice, this book contains over 200 practical exercises and their solutions, to develop the problem-solving abilities of process engineers. The problems were developed by the author during his many years of teaching at university and are kept brief, taken from the fields of instrumentation, modelling, plant control, control strategy design and stability of control. The algorithm flows and codes, which are mostly based on MATLAB', are given in many cases and allow for easy translation into applications. Since the text is structured according to'Applied Process Control: Essential Methods', all of the necessary background information on the underlying methods can be easily and quickly found in this accompanying book.
Print version record.
Keywords: Chemical process control; Electronic books